(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2020)
This article collects the main guidelines of our master’s thesis in Specific Didactics, at the Universidad Nacional del Litoral, entitled ‘The teaching of the temporal dimension in Ancient history textbooks. A study of their construction and use’. The aim was to understand how temporality is constructed and developed, as a theoretical category, in six selected textbooks for the teaching of Ancient history, published in three different normative contexts. The objectives pursued were, included, but not limited, to identify and describe concepts and representations of temporality in ancient history textbooks; to elaborate hypotheses on what criteria have been followed in the treatment of temporality and the selection/proposal of resources/activities of each one; to analyze and compare the treatment of temporality in different Ancient history textbooks (according to the publisher and the year of publication); and to understand the theories supporting the different proposals analyzed and what type of relationship they establish between researched/taught history.